The promise of quantum computing for population genetics and molecular ecology - Davinack, Andrew A. (Frontiers in Quantum Science and Technology, 2025)
Population geneticists increasingly confront a paradox: even with genome-scale datasets and advanced machine learning models, subtle population structure often remains undetected, particularly in systems with low diversity, high dispersal, or recent divergence. This Opinion article argues that quantum computing and quantum machine learning (QML) offer a fundamentally different computational paradigm that may overcome these limitations. By leveraging principles such as superposition, entanglement, and high-dimensional Hilbert space embeddings, quantum systems can represent and analyze complex genetic relationships in ways that classical tools cannot. I outline how QML approaches such as quantum support vector machines, clustering algorithms, and optimization frameworks can be applied to detect cryptic population structure, optimize model selection, and reveal hidden patterns in genomic data. I also propose a conceptual pipeline for integrating quantum tools into molecular ecology and offer a roadmap for interdisciplinary collaboration. As quantum computing advances rapidly across the sciences, now is the time for evolutionary biologists and ecologists to engage with this emerging frontier. Quantum approaches may not only increase computational power, but also shift how we interrogate biological data, and reframe our understanding of population structure and diversity.